Quantitative Evaluation of Rotational Wood Welding Joint Strength Based on Regression of Data Sets - Yun Xu; Xuejiao Wang; Aleksandr G. Chernykh; Roshchina I. Svetlana; Pavel S. Koval; Egor V. Danilov; Anatoly Y. Naichuk (BioResources)
This study aimed to enhance rotational wood welding technology by developing a simplified prediction model for pull-out strength. The key findings can offer a robust evaluation framework to advance rotational wood welding and expand its applications in woodworking. For instance, (1) A comprehensive database of 689 previously published trials was curated to identify key factors: substrate diameter, effective welded length, and substrate density. (2) Comparative analysis of test outcomes and predictive models revealed consistent trends, suggesting that modeling techniques for self-tapping wood screws could be applied to rotational wood welding joints. (3) Univariate linear regression validated the primary factors, leading to a multivariate model for predicting withdrawal capacity. Theoretical predictions closely matched empirical data, highlighting the model’s industrial applicability.